Femmes intersexes : Sujet politique extrême du féminisme - Bastien Charlebois, Janik (Recherches féministes, 2014)
L’intersexualité est déjà abordée depuis plusieurs années au sein des théories féministes, où elle est généralement présentée comme l’exemple par excellence de la construction des sexes. Cependant, les personnes intersexes y apparaissent peu comme sujets, les analyses militantes et universitaires qu’elles produisent de même que leurs projets politiques demeurant largement ignorés. Serait-ce que les personnes intersexes ne peuvent qu’être objet et non sujet du féminisme? En examinant différentes conceptions du « nous femmes » et en relevant les modes par lesquels les femmes intersexes sont façonnées par l’hétérosexisme, l’auteure envisage une compatibilité d’action politique en s’appuyant sur la lecture qu’offre Young du genre comme structure sérielle. Intersexuality has already been a common topic in feminist theory since a few years. It is generally submitted at the evidence per excellence of the construction of sex. However, intersex persons rarely appear as subjects, while their activist and academic analyses and their political projects largely remain ignored. Does this mean that intersex persons can only be objects and not subjects of feminism? Through an examination of different conceptions of « us, women », as well as through an introduction to the ways intersex women are shaped by heterosexism, we envision Young’s gender as seriality proposal as offering legitimacy for common political action.
Donné en lecture au cours POL4212.
Keywords: cours; discipline; fem1000; identités LGBTQIA2+; lit4700; militance; ontologie; personnes intersexes; pol4212; premier cycle; ressource en ligne; sciences humaines; soc2014; sociologie; thématiques; épistémologie

The SAGE handbook of feminist theory - Evans, Mary (SAGE reference, 2014)
At no point in recorded history has there been an absence of intense, and heated, discussion about the subject of how to conduct relations between women and men. This Handbook provides a comprehensive guide to these omnipresent issues and debates, mapping the present and future of thinking about feminist theory. The chapters gathered here present the state of the art in scholarship in the field, covering: Epistemology and marginality; Literary, visual and cultural representations; Sexuality; Macro and microeconomics of gender; Conflict and peace. The most important consensus in this volume is that a central organizing tenet of feminism is its willingness to examine the ways in which gender and relations between women and men have been (and are) organized. The authors bring a shared commitment to the critical appraisal of gender relations, as well as a recognition that to think ‘theoretically’ is not to detach concerns from lived experience but to extend the possibilities of understanding. With this focus on theory and theorizing about the world in which we live, this Handbook asks us, across all disciplines and situations, to abandon our taken-for-granted assumptions about the world and interrogate both the origin and the implications of our ideas about gender relations and feminism. It is an essential reference work for advanced students and academics not only of feminist theory, but of gender and sexuality across the humanities and social sciences.
Le chapitre Boyle, K. (2014). Feminism and pornography (pp. 215-231) a été donné en lecture au cours SEX1911.
Keywords: approches et analyses; corps; cours; discipline; har4600; histoire et politique; intersectionnalité; outils; ouvrages de références; philosophie; phénoménologie; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences de la gestion; sciences humaines; sciences sociales; sex1911; thématiques; violences; économie; épistémologie; études féministes